Human U1 RNA genes contain an unusually sensitive nuclease S1 cleavage site within the conserved 3' flanking region. - Htun, H (1984)
We find that the cloned DNAs of human U1 small nuclear RNA genes contain two nuclease S1-sensitive sites, one about 1.8 kilobases downstream of the U1 RNA coding region and the other around 0.3 kilobase upstream. The downstream site is unusually sensitive to the nuclease, being cleaved in both linear and negatively supercoiled DNAs. The extent of cleavage at this site is enhanced at lower pH and reduced concentrations of NaCl; the effects of salt are more apparent on linear than supercoiled DNAs. The nuclease S1 sensitivity of this downstream site is dependent on the presence of the sequence (dC-dT)n X (dA-dG)n, where n = 15-25. (One gene with n = 5 is resistant to nuclease S1 cleavage in this region.) In contrast, the nuclease S1 site upstream of the coding region is cleaved only when the DNA is supercoiled. This site also has a homopyrimidine X homopurine bias in the DNA strands, but the sequence is less regular. In the course of these studies, we detected several discrepancies between our restriction maps of some U1 RNA genes and those published by others. Our maps demonstrate that all seven cloned human U1 RNA genes are very similar in sequence for as much as 2.3 kilobases downstream of the U1 RNA coding region.